Relationship between Medical Students' Perceived Stress and Gaming Behavior at King Saud University. (1st December 2022) - Almigbal, Turky H.; Alrasheed, Abdullah A.; Almutairi, Ebtesam S.; Alrehaili, Rawan A.; Alzahrani, Arwa M.; Alhassan, Nourah A.; Aldekhyyel, Ranyah; Batais, Mohammed A.
Abstract : Gaming addiction has gradually developed among medical students and has been a contentious topic for nearly a decade. This study is aimed at estimating the prevalence of gaming addiction among medical students at King Saud University and examining the relationship between perceived stress levels and gaming addiction. We conducted a cross-sectional study among 370 students from 2019 to 2020 using a self-reporting questionnaire consisting of two validated test scales: the Gaming Disorder Test and the Perceived Stress Scale. The questionnaire was sent to all students through an email. Descriptive analyses and t -test statistical tests were used in this study. The prevalence rate of gaming addiction was found to be 4.6%, while the prevalence of perceived stress was confirmed at 95.9%. Students with excellent GPAs and high family income were associated (p < 0.001 ). Younger groups, females, and students with high family incomes showed higher levels of perceived stress than others. According to Pearson's correlation, gaming addiction was not significantly correlated with stress among medical students (p > 0.05 ). According to chi-square test also, no significant association was found between gaming disorder and perceived stress (χ 2 = 4.412 ; p = 0.353 ). In conclusion, gaming addiction among medical students has scored low prevalence, indicating gaming is not a factor contributing to stress among this group. The high level of perceived stress among medical students should draw attention to the provision of regular psychological care.